Decision-making applications in food safety and food defense - Krusemark, Kathryn S. (Kansas State University, 2009)
The Department of Homeland Security recognizes the Agriculture and Food Sector as a Critical Infrastructure and Key Resource—critical to the health and wealth of the United States. When food safety (i.e., unintentional) or food defense (i.e., intentional) issues arise, those in the Agriculture and Food Sector must quickly and efficiently make decisions to ensure the safety of consumers. Decision-making is an essential element in critical infrastructure protection and response. Naturalistic decision-making (NDM) explores how people make decisions in real- world settings. Eight factors characterize the task and setting in naturalistic environments and include the following: ill-structured problems; uncertain, dynamic environments; shifting, ill-defined, or competing goals; action/feedback loops; time constraints; outcome with high stakes; multiple players; and organizational goals and norms. This thesis explores whether or not food safety and food defense educational programs incorporate methods that help professionals make good decisions. To that end, this thesis first examines the decision-making environment in responding to incidents involving food safety and food defense. Four cases involving food safety and food defense reveal the presence of all eight factors. As these factors complicate the decision-making process, this thesis then evaluates whether or not prevailing educational programs and tools aimed at preparing for food safety and food defense issues (i.e., HACCP and CARVER plus Shock) directly address the eight factors characterizing NDM settings. This is explored by “following” a hypothetical student in a food safety and food defense course. The information presented to the student was analyzed and this analysis indicates that the eight factors characterizing NDM settings were addressed albeit to varying degrees. HACCP addresses action/feedback loops, time constraints, outcome with high stakes, and multiple players. CARVER plus Shock addresses action/feedback loops, outcome with high stakes, and multiple players. While HACCP somewhat addresses ill-structured problems and organizational goals and norms, it fails to address uncertain, dynamic environments and shifting, ill-defined, or competing goals. CARVER plus Shock somewhat addresses ill-structured problems; uncertain, dynamic environments; shifting, ill-defined, or competing goals; time constraints; and organizational goals and norms. In light of this, new approaches to training are needed to fully incorporate all eight factors.
Keywords: Food safety; Food defense; Decision-making; Homeland Security; Food and Agriculture; Agriculture, Food Science and Technology (0359)